Ownership institutional and firm value: the mediating role of profitability in Indonesian firms - Rachmat, Radhi Abdul Halim; Hendayana, Yana (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Institutional ownership refers to the shareholding structure and the parties that own or control a company. Institutional ownership can be interpreted as ownership of company shares owned by institutions. In this case, institutions refer to legal entities such as corporations, banks, insurance companies, and others. This study aims to research related to management that continues to grow. The research method used is quantitative research. This study provides a clear picture of the effect of institutional ownership of the company through profitability. The research was conducted on all companies listed on the Indonesia Stock Exchange from 2015 to 2018. The sample used in this study consisted of 322 companies selected using a purposive sampling method. Data processing uses mediation analysis with the SPSS 24 application with the additional PROCESS feature by Hayes. The results showed that, first, institutional ownership affects firm value. Second, profitability mediates the effect of institutional ownership on firm value.